3D printing materials and functional components used in renewable energy applications - Muñoz Zuñiga, Aissa Olenka; Macedo Meza, Carlos Enrique (LACCEI, 2025)
3D printing technology is revolutionizing the world as we know it. The depletion of fossil fuels, increasing energy demand and climate change are problems that demand viable and sustainable long-term solutions. Under these circumstances, the use of additive manufacturing in renewable energy presents itself as a favorable alternative to address this crisis. Therefore, the purpose of this study is to present a systematic literature review based on 3D printing materials and devices or functional components used in renewable energy applications. In order to achieve this goal, the PICOC method was employed with the final retrieval of the selection of articles through the PRISMA methodology. A total of 605 records from 4 indexed databases were identified from the search performed. The variability of materials used in 3D printing is highlighted, including polymeric materials, ceramics, metals, composites, materials of biological origin, recyclable and waste materials, where they play a transforming role in the circular economy. Also, applications of 3D printing are highlighted in devices or functional components for the use of four different renewable energies: wind, marine, bioelectrochemical and solar-electrochemical; where design and manufacturing flexibility are the main advantages exploited. Finally, the coupling of additive manufacturing to other existing and developing technologies has the capacity to drive and generate new routes towards a sustainable energy transition.